Could Increased Expression of Hsp27, an “Anti-Inflammatory” Chaperone, Contribute to the Monocyte-Derived Dendritic Cell Bias towards Tolerance Induction in Breast Cancer Patients? - de Azevedo-Santos, Ana Paula Silva; Rocha, Mirtes Castelo Branco; Guimarães, Sulayne Janayna Araujo; Vale, André Alvares Marques; Laginha, Fabio Martins; Nascimento, Flavia Raquel F.; Nagai, Maria Aparecida; Bergami-Santos, Patrícia C.; Barbuto, José Alexandre Marzagão (Mediators of Inflammation, 2019)
Dendritic cells (DCs) are the most efficient antigen-presenting cells and link the innate immune sensing of the environment to the initiation of adaptive immune responses, which may be directed to either acceptance or elimination of the recognized antigen. In cancer patients, though DCs would be expected to present tumor antigens to T lymphocytes and induce tumor-eliminating responses, this is frequently not the case. The complex tumor microenvironment subverts the immune response, blocks some effector mechanisms, and drives others to support tumor growth. Chronic inflammation in a tumor microenvironment is believed to contribute to the induction of such regulatory/tolerogenic response. Among the various mediators of the modulatory switch in chronic inflammation is the “antidanger signal” chaperone, heat shock protein 27 (Hsp27), that has been described, interestingly, to be associated with cell migration and drug resistance of breast cancer cells. Thus, here, we investigated the expression of Hsp27 during the differentiation of monocyte-derived DCs (Mo-DCs) from healthy donors and breast cancer patients and evaluated their surface phenotype, cytokine secretion pattern, and lymphostimulatory activity. Surface phenotype and lymphocyte proliferation were evaluated by flow cytometry, interferon- (IFN-) γ, and interleukin- (IL-) 10 secretion, by ELISA and Hsp27 expression, by quantitative polymerase chain reaction (qPCR). Mo-DCs from cancer patients presented decreased expression of DC maturation markers, decreased ability to induce allogeneic lymphocyte proliferation, and increased IL-10 secretion. In coculture with breast cancer cell lines, healthy donors’ Mo-DCs showed phenotype changes similar to those found in patients’ cells. Interestingly, patients’ monocytes expressed less GM-CSF and IL-4 receptors than healthy donors’ monocytes and Hsp27 expression was significantly higher in patients’ Mo-DCs (and in tumor samples). Both phenomena could contribute to the phenotypic bias of breast cancer patients’ Mo-DCs and might prove potential targets for the development of new immunotherapeutic approaches for breast cancer.